Field Epidemiology Training Program Response to COVID-19 During a Conflict: Experience From Yemen - Al Serouri, Abdulwahed Abduljabar; Ghaleb, Yasser Ahmed; Al Aghbari, Labiba Anam; Al Amad, Mohammad Abdullah; Alkohlani, Abdulhakem Sharaf; Almoayed, Khaled Abdullah; Jumaan, Aisha Obad (Frontiers in Public Health, 2021)
COVID-19 pandemic has underscored the need for a well-trained public health workforce to save lives through timely outbreaks detection and response. In Yemen, a country that is entering its seventh year of a protracted war, the ongoing conflict severely limited the country’s capacity to implement effective preparedness and response measures to outbreaks including COVID-19. There are growing concerns that the virus may be circulating within communities undetected and unmitigated especially as underreporting continues in some areas of the country due to a lack of testing facilities, delays in seeking treatment, stigma, difficulty accessing treatment centers, the perceived risks of seeking care or for political issues. The Yemen Field Epidemiology Training Program (FETP) was launched in 2011 to address the shortage of a skilled public health workforce, with the objective of strengthening capacity in field epidemiology therefore that events of public health importance can be detected and investigated in a timely and effective manner. During the COVID-19 pandemic, the Yemen FETP’s response has been instrumental through participating in country-level coordination, planning, monitoring, and developing guidelines/standard operating procedures and strengthening surveillance capacities, outbreak investigations, contact tracing, case management, infection prevention, and control, risk communication, and research. As the second wave is circulating with a steeper upward curve than the first one, the country will not be able to deal with a surge of cases as secondary care is extremely crippled. Therefore, prevention and control are the only tools available to reduce the impact of COVID-19 on morbidity and mortality and the health partners should support the Yemen FETP to continue its role in increasing surveillance capacity, rapid response to outbreaks, and strengthening a health system to be able to respond to future epidemics. Other measures to address COVID19 impact on other public health priorities, refining messaging to encourage behavioral change, and boosting ICU capacity should not be forgotten.